Sustainable Landscapes Rating Tool (SLRT) - CGIAR Research Program on Forests, Trees and Agroforestry (2018)
EII, CIFOR, and the Governors’ Climate and Forests Task Force (GCF-TF) are collaborating on jurisdictional approaches; and CIFOR implemented SLRT in 4 states/provinces in Brazil, 5 in Peru, 4 in Mexico, 1 in Ecuador, 2 in Cote d’Ivoire, and 3 in Indonesia. Summary profiles of 18 sub-national jurisdictions: https://earthinnovation.org/state-of-jurisdictional-sustainability/